The implications of automation for economic growth and the labor share - Klaus Prettner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
We introduce automation into a standard model of capital accumulation and show that (i) there is the possibility of perpetual growth, even in the absence of technological progress; (ii) the long-run economic growth rate declines with population growth, which is consistent with the available empirical evidence; (iii) there is a unique share of savings diverted to automation that maximizes long-run growth; (iv) the labor share declines with automation to an extent that fits to the observed pattern over the last decades.
urn:nbn:de:bsz:100-opus-12880
Keywords: O11; O33; O41; 330; automation; robots; machine learning; perpetual economic growth; declining labor share; inequality